New strategies for the production of butanol - Gallardo, R. (2012)
Increasing demand for the use of renewable resources as feedstock for the production of chemicals combined with advances in biotechnology is generating a renewed interest in fermentative butanol production. In this sense, glycerol that is a byproduct of biodiesel production arises as a potential substrate for butanol production. In this work, Clostridium pasteurianum DMS 525 has been studied for butanol production in batch fermentation (serum bottles) using pure and crude glycerol. Although the strain produces acids as a way of energy generation, the main products found were butanol, and 1,3-propanediol (1,3-PDO). Moreover, the competitive nature of butanol and 1,3-PDO pathways has been evident, and a shift to butanol pathway for higher glycerol concentrations was clearly observed. Optimization of culture medium has been conducted yielding a maximum butanol production and glycerol consumption of 9,5 g/l and 40 g/l, respectively. Iron was found to play a key role and its limitation inhibits butanol production. Supplementation of 3 mg/l FeCl2.7H2O in the culture medium led to 140% increase in butanol production, which is likely related to ironcontaining alcohol dehydrogenases involved in the process. Results suggest that glycerol consumption is not affected by nutrient limitation but by product inhibition. To improve butanol tolerance of C. pasteurianum, random chemical mutagenesis in solid medium was performed. Although it was possible to grow cells at 12 g/l butanol (except in the control), butanol production and glycerol consumption were not affected. Finally, isolation of butanol resistant consortia from granular sludge has been achieved. The methodology involved cell culturing under butanol stress conditions in liquid and solid media resulting in five butanol-producing cultures. Molecular biology analyses are being carried out to characterize these consortia. Results obtained provide a deeper understanding of a complex process as the anaerobic fermentation of glycerol using clostridia. C. pasteurianum shows a great potential for butanol production from crude glycerol. Nevertheless, butanol toxicity seriously limits butanol titer, thus it is important to find ways to overcome this problem. Future work includes further media optimization, experiences in reactors with pH control and directed mutagenesis for knocking out genes that could lead to a higher butanol production.